Can rectal endoscopic sonography be used to predict infiltration depth in patients with deep infiltrating endometriosis of the rectum?. (March 2014) - Rossi, L.; Palazzo, L.; Yazbeck, C.; Walker, F.; Chis, C.; Luton, D.; Koskas, M.
ABSTRACT Objectives To evaluate the diagnostic accuracy of rectal endoscopic sonography (RES) in the prediction of the infiltration depth of rectal endometriosis and to ascertain whether RES could be used to choose between segmental bowel resection and a more conservative approach, such as shaving or discoid resection. Methods In this retrospective study, 38 consecutive patients with symptomatic deep infiltrating endometriosis of the rectum who underwent laparoscopic colorectal resection were included. RES results for infiltration depth of rectal endometriosis were compared with results of pathological examination. The sensitivity, specificity, positive and negative predictive values (PPV and NPV, respectively), positive and negative likelihood ratios (LRs) and test accuracy were calculated for the presence of infiltration of the muscularis layers and submucosal/mucosal layers, as demonstrated by RES and confirmed by histopathological analysis. Results For the detection of muscularis layer infiltration by endometriosis, the PPV of RES was 100%, whereas for the detection of submucosal/mucosal layer involvement, the sensitivity was 89%, specificity was 26%, PPV was 55%, NPV was 71%, test accuracy was 58% and positive and negative LRs were 1.21 and 0.40, respectively. Conclusions RES is a valuable tool for detecting rectal endometriosis as endometriotic infiltration of the muscularis layer can be predicted accurately. However, RES is less accurate in detecting submucosal/mucosal layer involvement and cannot, therefore, be used to choose between bowel resection and a more conservative approach. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd